Evaluation of the quality of cyanoacrylate adhesive joints using the example of poly(methyl methacrylate) and polycarbonate - Mazur Piotr (Production Engineering Archives, 2017)
Adhesive bonding is one of the simplest and most common methods used for joining materials. It is applied in both production and repair works. The most commonly used adhesives are cyanoacrylates, due to the possibility of combining various materials and short curing time. One of the ways to assess the quality of the adhesive used is testing the shear strength of bonded joints. Three adhesives commonly available on the Polish market, from various manufacturers and with different prices per gram of product were tested. The polymer materials bonded were poly(methyl methacrylate) and polycabonate, since they are broadly used in the automotive industry and household equipment. The study revealed significant differences in bonding strength, reaching as much as 38% The adhesive’s price was not commensurate with the quality of the product tested in all cases.